Influence of Flexible Classroom Seating on the Wellbeing and Mental Health of Upper Elementary School Students: A Gender Analysis - Bluteau, Jonathan; Aubenas, Solène; Dufour, France (Frontiers in Psychology, 2022)
This article presents the results of a study examining the influence of flexible seating on the well-being and mental health of elementary school students. While traditional seating (also known as fixed seating/ fixed classroom) remains the preferred classroom seating arrangement for teachers, a new type of seating arrangement is becoming more common in schools: the flexible classroom (also known as flexible seating). The purpose of this type of arrangement is to meet the needs of students by providing a wide variety of furniture to allow them to make choices based on their preferences and the objectives of the task at hand. The furniture is arranged to encourage movement, the use of space, and a positive classroom environment. This article presents the results of exploratory research conducted in Quebec among Grade 5 and 6 students comparing the well-being and mental health of students in fixed and flexible classrooms. Furthermore, the study included a gender-differentiated analysis for each group. It is based on a quasi-experimental, quantitative design with post-test only and a control group. The study was conducted with 107 students in three Grade 5 and 6 flexible classrooms (n = 51) and three Grade 5 and 6 fixed classrooms (n = 56). The results showed that flexible classroom seating had a positive influence on the girls’ well-being and mental health. In contrast, for the boys, fixed classroom seating was most conducive to their well-being and mental health. However, our study has some limitations that are discussed in the article.